Biologically-relevant Staphylococcus aureus biofilm phenotype characterization and liability to novel antibiofilm drugs - Shaimaa Wahman; Riham Mahmoud Shawky; Mohamed Emara (Journal of the Pakistan Medical Association, 2023)
N/A